Brief cycling intervals incrementally increase the number of hematopoietic stem and progenitor cells in human peripheral blood - Pradana, Fendi; Nijjar, Tarondeep; Cox, Phoebe A.; Morgan, Paul T.; Podlogar, Tim; Lucas, Samuel J. E.; Drayson, Mark T.; Kinsella, Francesca A. M.; Wadley, Alex J. (Frontiers in Physiology, 2024)
Introduction: Peripheral blood stem cell (PBSC) donation is the primary procedure used to collect hematopoietic stem and progenitor cells (HSPCs) for hematopoietic stem cell transplantation. Single bouts of exercise transiently enrich peripheral blood with HSPCs and cytolytic natural killer cells (CD56dim), which are important in preventing post-transplant complications. To provide a rationale to investigate the utility of exercise in a PBSC donation setting (≈3 hours), this study aimed to establish whether interval cycling increased peripheral blood HSPC and CD56dim concentrations to a greater degree than continuous cycling. Methods: In a randomised crossover study design, eleven males (mean ± SD: age 25 ± 7 years) undertook bouts of moderate intensity continuous exercise (MICE, 30 min, 65-70% maximum heart rate (HRmax)), high-volume high intensity interval exercise (HV-HIIE, 4 x 4 min, 80-85% HRmax) and low-volume HIIE (LV-HIIE, 4 x 2 min, 90-95% HRmax). The cumulative impact of each interval on circulating HSPC (CD34+CD45dimSSClow) and CD56dim concentrations, and the bone marrow homing potential of HSPCs (expression of CXCR-4 and VLA-4) were determined. Results: There was an increase in HSPC concentration after two intervals of LV-HIIE (Rest: 1.84 ± 1.55 vs. Interval 2: 2.94 ± 1.34, P = 0.01) and three intervals of HV-HIIE only (Rest: 2.05 ± 0.86 vs. Interval 3: 2.51 ± 1.05, P = 0.04). The concentration of all leukocyte subsets increased after each trial, with this greatest for CD56dim NK cells, and in HIIE vs. MICE (LV-HIIE: 4.77 ± 2.82, HV-HIIE: 4.65 ± 2.06, MICE: 2.44 ± 0.77, P < 0.0001). These patterns were observed for concentration, not frequency of CXCR-4+ and VLA-4+ HSPCs, which was unaltered. There was a marginal decrease in VLA-4, but not CXCR-4 expression on exercise-mobilised HSPCs after all trials (P < 0.0001). Discussion: The results of the present study indicate that HIIE caused a more marked increase in HSPC and CD56dim NK cell concentrations than MICE, with mobilised HSPCs maintaining their bone marrow homing phenotype. LV-HIIE evoked an increase in HSPC concentration after just 2 x 2-minute intervals. The feasibility and clinical utility of interval cycling in a PBSC donation context should therefore be evaluated.